Структура фурано-эпоксидных композитов: фрактально-перколяционный подход - Рассоха, Алексей Николаевич; Черкашина, Анна Николаевна (НТУ "ХПИ", 2012)
In terms of percolation theory the structure of the furan-epoxy construction composites is analyzed. The main parameters of the composites structure taking into account the emerging fractal percolation cluster consisting of particles dispersed filler are identified.
Keywords: композиционные материалы; фурано-эпоксидные композиты; реакционноспособный олигомер; ФАЭД-50(20); аминофенольный отвердитель; Агидол АФ-2; наполнители дисперсные; кварцевый песок; перколяция; неупорядоченные системы